Establishment of the MID‐NET® medical information database network as a reliable and valuable database for drug safety assessments in Japan. Issue 10 (29th August 2019) - Yamaguchi, Mitsune; Inomata, Satomi; Harada, Sayoko; Matsuzaki, Yu; Kawaguchi, Maiko; Ujibe, Mayuko; Kishiba, Mari; Fujimura, Yoshiaki; Kimura, Michio; Murata, Koichiro; Nakashima, Naoki; Nakayama, Masaharu; et al.
Abstract: Purpose: To establish a new medical information database network (designated MID‐NET ® ) to provide real‐world data for drug safety assessments in Japan. Methods: This network was designed and developed by the Ministry of Health, Labour and Welfare and the Pharmaceuticals and Medical Devices Agency in collaboration with 23 hospitals from 10 healthcare organizations across Japan. MID‐NET ® is a distributed and closed network system that connects all collaborative organizations through a central data center. A wide variety of data are available for analyses, including clinical and administrative information. Several coding standards are used to standardize the data stored in MID‐NET ® to allow the integration of information originating from different hospitals. A rigorous and consistent quality management system was implemented to ensure that MID‐NET ® data are of high quality and meet Japanese regulatory standards (good post‐marketing study practice and related guidelines). Results: MID‐NET ® was successfully established as a reliable and valuable medical information database and was officially launched in April 2018. High data quality with almost 100% consistency was confirmed between original data in hospitals and the data stored in MID‐NET ® . A major advantage is that approximately 260 clinical laboratory test results are available for analysis. Conclusions: MID‐NET ® is expected to be a major data source for drug safety assessments in Japan. Experiences and best practices established in MID‐NET ® may provide a model for the future development of similar database networks.